They do pay! Event merchandise attributes that affect sales and profits at a folk festival. (25th September 2020) - Dodds, Rachel; Jenkins, Brittany; Smith, Wayne W.; Pitts, Robert E.
The need to make profit affects the overall ability of a festival to operate. Merchandise sales are one way to increase revenue and also promote a festival. This study conducted a field experiment to test willingness to pay theory at the Canadian Mariposa Folk Festival. Results indicated that personal sales efforts, Canadian and sustainability branded merchandise increased sales and profitability. Implications from this study demonstrate that brands that match the market sell best but festival managers need to understand their market and their margins if they wish to capitalise on increased revenues.